Institutional Ownership and Corporate Tax Avoidance: New Evidence - Khan, Mozaffar; Srinivasan, Suraj; Tan, Liang (The Accounting Review, 2017)
ABSTRACT We provide new evidence on the agency theory of corporate tax avoidance (Slemrod 2004; Crocker and Slemrod 2005; Chen and Chu 2005) by showing that increases in institutional ownership are associated with increases in tax avoidance. Using the Russell index reconstitution setting to isolate exogenous shocks to institutional ownership, and a regression discontinuity design that facilitates sharper identification of treatment effects, we find a significant and discontinuous increase in tax avoidance following Russell 2000 inclusion. The tax avoidance involves the use of tax shelters, and immediate benefits include higher profit margins and likelihood of meeting or beating analyst expectations. Collectively, the results shed light on the effect of increased ownership concentration on tax avoidance.